Detection of Gas6/AXL complex and its expression changes in patients with ST-segment elevation myocardial infarction - Yin, Zhao; Nie, Xiaohua; Li, Tianlun; Zhao, Bei; Wang, Shouli; Zhang, Liguo; Zhang, Xuyuan; Shan, Zhaoliang (Frontiers in Medicine, 2025)
IntroductionIt has been reported Gas6/AXL pathway participates in several diseases. However, due of the lack of specific antibody, the significance and change circulatory Gas6/AXL complex in related diseases remain unclear.MethodsThe mice were immunized with human AXL protein which were expressed by L cells to obtain monoclonal antibodies (mAbs). The flow cytometry was used to monoclonal antibodies screening and binding region mapping. To prepare an AXL-Gas6 specific mAb coated ELISA plate, and test the level of AXL-Gas6 complex in human blood.Results and discussionWe successfully obtained an AXL monoclonal antibody only binding to Gas6/AXL complex. Using the antibody, we firstly found that AXL expressed on human pDCs had bind to Gas6. Not only applicated in flow cytometry, this novel antibody could also be used as capture antibody in ELISA. Depend on this antibody, we firstly discovered that sAXL Gas6 complex was significantly increased in patients with AMI. Compared to AXL detected by commercial kit, AXL-Gas6 complex we measured emerged as a more sensitive biomarker and risk factor for patients with ST-segment elevation myocardial infarction.